Kadar Puncak (Cmax), Waktu Puncak (Tmax), Waktu Paruh (T½) dan Bersihan Teobromin pada Sukarelawan Sehat setelah Pemberian Dark Chocolate Bar Per Oral - Nyoman Defriyana Suwandi; Cholis Abrori; Muhammad Hasan (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Dark chocolate contains two derivates of metilxantin, I.e. caffeine (1,3,7-trimetilxantin) and theobromine (3,7 dimetilxantin). Theobromine can be found in plasma. Theobromine concentration in plasma determined not only by drug dosage but also by pharmacokinetic parameters. This research aimed to determine pharmacokinetic parameters by using HPLC (High Performace Liquid Chromatography) method. This study used Quasi Experimental Design by using 16 plasma samples collected at the 0, 1.5, 3, 6, 10, 24 hours. The pharmacokinetic parameter calculations were obtained from the polynomial curve and linear curve of drug concentration in plasma by time. The maximum concentration (Cmax) theobromine on plasma after consumption of dark chocolate bar per oral was 4.173 mg/L. The maximum time (Tmax) was at the 2.501 hours. The half time (t½) theobromine was 4.880 hours. Theobromine clearance in plasma was 14.2 ml/kg/hour. The study has reported pharmacokinetic parameters of theobromine in plasma after eating dark chocolate bars orally. Keywords: Chocolate, half-time, maximum concentration, maximum time, theobromine